Peer Mentoring as a Tool for Developing Soft Skills in Clinical Practice: A 3-Year Study - Antonio M. Lluch; Clàudia Lluch; María Arregui; Esther Jiménez; Luis Giner-Tarrida (MDPI AG, 2021)
Education currently focuses on improving academic knowledge and clinical skills, but it is also important for students to develop personal and interpersonal skills from the start of their clinical practice. The aim was to evaluate the effect of peer mentoring in third-year students and to gauge the evolution of non-technical skills (NTS) acquisition up to the fifth year. The study groups were selected between September 2015 and May 2018, based on the NTS training they had or had not received: (1) fifth-year students with no training (G1); (2) third-year students mentored in NTS (G2a); and (3) a small group of fifth-year students who became mentors (G2b). A total of 276 students who took part in this study were assessed using a 114-item self-evaluation questionnaire. Data were collected from seven surveys conducted between September 2015 and May 2018, and statistical analysis was performed using one-way ANOVA and Fisher's post-hoc test. G2a improved their non-technical skill acquisition over three years of clinical training up to their fifth year. This group and G2b showed statistically significant differences compared to non-mentored students (G1). Peer mentoring at the beginning of clinical practice is a valid option for training students in non-technical skills.